A global analysis of the operation and maintenance role on the placing of wave energy farms. (December 2015) - Guanche, R.; de Andrés, A.; Losada, I.J.; Vidal, C.
Highlights: A global analysis of the O&M main indicators is carried out. Availability and accessibility levels in different regions of the world are studied. Accessibility has a high dependency on the wave height threshold. There are high resource sites valid for mature technologies with low failure rates. Milder locations are recommended for higher failure rates due to lower O&M costs. Abstract: In this work an analysis of suitable locations for the development of wave energy farms is carried out based on representative operation and maintenance parameters. The analysis is applied globally on the basis of long-term global climate data set. Availability and accessibility levels are assessed first by considering different wave height thresholds. Secondly, the O&M access limits are quantified in terms of the weather windows and waiting period between them considering different windows lengths and scenarios. Finally, the O&M cost per kW h is calculated for a wave energy converter based on a point absorber concept. O&M costs has been calculated following the methodology proposed on Guanche et al. (2014). As expected, results show that locations with mild wave climate have very low O&M costs per kW h. Some areas with high wave resource, such as Scotland, Spain or Nova Scotia present reasonable O&M costs compared to the power production in these areas. However, other locations with high resource like Chile or Australia resulted in extremely high O&M costs due to the inaccessibility of these sites during long periods of time.